A study on feasibility of problem based learning at university level - Ahmed, Zulfiqar; Khatoon, Sufiana (Penerbit Universiti Kebangsaan Malaysia, 2014)
The study was designed to investigate the perceptions of university teachers for feasibility of problem based learning at university level. Being a descriptive study a questionnaire was used as a tool to acquire perceptions of university teachers regarding feasibility of problem based learning at university level. A purposive sample of 23 university teachers from two departments i.e. Education & Mass communication at university was selected including some senior faculty members. Participants were with different qualifications which ranged from masters to MS/PhDs. Data was analyzed through descriptive statistics and by calculating a t-test to determine the difference of perceptions among university teachers in view of their gender. Results indicated a strong perception of university teachers about effectiveness of problem based learning on student. It was also found that university teachers were having strong perceptions about initiation of problem based learning at university level. There was no significant difference about perceptions of teachers in view of their gender. Necessary changes in curriculum, assessment procedures, training of staff, administrative needs and raising of funding resources were recommended for initiation of problem based learning at university campus.